An overview of the below knee prosthesis socket fabrication made from natural fiber composite - Irawan, Agustinus Purna; Utama, Didi Widya; Setiawan, Antonius Singgih; Fitriyana, Deni Fajar; Wicaksana, Yazid Surya; Priyani, Putri Agustin; Anis, samsudin; Cionita, Tezara; Siregar, Januar Parlaungan; Jamiluddin, Jaafar; Manalu, Janviter; Numberi, Johni Jonatan (Penerbit UTHM, 2024)
The prevalence of disability in Indonesia is considerable, necessitating a significant demand for prosthetic limbs in the country. In addition, the global demand for prosthetics continues to increase due to several factors such as wars, disasters, and the prevalence of chronic diseases. This article presents an overview of the manufacturing processes involved in the production of socket prostheses using natural fiber composite materials. Prosthetic sockets play an important role in meeting the needs of individuals who have undergone limb amputation. The findings from this study indicate that the manufacturing of prosthetic sockets requires consideration of characteristics such as comfort, functionality, biocompatibility, and flexibility. The utilization of natural fiber composites in the production of prosthetic sockets has several benefits, including cost-effectiveness, weight reduction, and biodegradation, making it a sustainable alternative for prosthetic socket fabrication. The utilization of natural fiber composites in the fabrication of socket prostheses has been the subject of much discussion, with particular emphasis on the influence of various matrices, reinforcing materials, and manufacturing methods on the characteristics and attributes of socket prostheses made from natural fiber composites.